Association of airborne particles, protein, and endotoxin with emergency department visits for asthma in Kyoto, Japan - Mohammad Shahriar Khan; Souleymane Coulibaly; Takahiro Matsumoto; Yoshitaka Yano; Makoto Miura; Yukio Nagasaka; Masayuki Shima; Nobuyuki Yamagishi; Keiji Wakabayashi; Tetsushi Watanabe (Komiyama Printing Co. Ltd, 2018)
Abstract Background The health effects of biological aerosols on the respiratory system are unclear. The purpose of this study was to clarify the association of airborne particle, protein, and endotoxin with emergency department visits for asthma in Kyoto City, Japan. Methods We collected data on emergency department visits at a hospital in Kyoto from September 2014 to May 2016. Fine (aerodynamic diameter ≤ 2.5 μm) and coarse (≥ 2.5 μm) particles were collected in Kyoto, and protein and endotoxin levels were analyzed. The association of the levels of particles, protein, endotoxin, and meteorological factors (temperature, relative humidity, wind speed, and air pressure) with emergency department visits for asthma was estimated. Results There were 1 to 15 emergency department visits for asthma per week, and the numbers of visits increased in the autumn and spring, namely many weeks in September, October, and April. Weekly concentration of protein in fine particles was markedly higher than that in coarse particles, and protein concentration in fine particles was high in spring months. Weekly endotoxin concentrations in fine and coarse particles were high in autumn months, including September 2014 and 2015. Even after adjusting for meteorological factors, the concentrations of coarse particles and endotoxin in both particles were significant factors on emergency department visits for asthma. Conclusions Our results suggest that atmospheric coarse particles and endotoxin are significantly associated with an increased risk of asthma exacerbation.